Dynamic scaffolding in a cloud-based problem representation system. Issue 5 (28th October 2014) - Beng Lee, Chwee; Voon Ling, Keck; Reimann, Peter; Ahmad Diponegoro, Yudho; Heng Koh, Chia; Chew, Derwin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to argue for the need to develop pre-service teachers' problem solving ability, in particular, in the context of real-world complex problems. Design/methodology/approach – To argue for the need to develop pre-service teachers' problem solving skills, the authors describe a web-based problem representation system that is embedded with levels of scaffolding to support the claim. Findings – The authors' conceptualisation of this cloud-based environment is also very much aligned with the development of pre-service teachers' systems thinking. Teacher learning itself is a complex system that involves many processes, mechanisms and interactions of elements, and the outcomes may be highly unpredictable (Opfer and Pedder, 2011). As a result of the complex nature of teacher learning, it would be meaningful to frame teacher learning as a complex system. An approach to enable pre-service teachers to be aware of this complexity is to situate them in a systems thinking context. Originality/value – This paper discusses a system which was developed for problem solving. The levels of adaptive scaffoldings embedded within the system is an innovation which is not found in other similar research projects.